The future of care and healthcare provision to community-dwelling disabled elderly people in an ageing society - Susło, Anna; Mizia, Sylwia; Horoch-Łyszczarek, Ewa; Pochybełko, Ewa (Family Medicine & Primary Care Review, 2023)
The populations of all European countries are ageing at an increasing age, especially in rural areas, where the process overlaps with emigration to urban areas, which additionally depletes the elderly residents of social support while the ability to perform everyday activities becomes progressively limited with age. A literature review was been carried out in order to identify the characteristics of modern technology-based tools for providing care and healthcare to community-dwelling people sixty years old and older. Home-based care is preferred over institutional care, including in nursing homes, by about 90% of the elderly. Home-based care, diagnostics, and monitoring limit the financial and organizational pressure on the healthcare system. Care and rehabilitation procedures are carried out under the direct supervision of specialized medical staff at respective offices or centers while they can be evaluated and supervised remotely, without the need for scarce medical staff to be constantly present with the patient, and without the requirement for the patient to be transported back and forth. The problem of providing care and healthcare to the increasing number of disabled elderly within the constraints of the available budget and with scarce qualified staff can be resolved only through the broad application of solutions based on information technology (IT), which benefit from the dynamic growth of the Internet-of-Things, including the Internet-of-Medical-Things (IoMT) and Artificial Intelligence (AI). This will allow longer home-based care, which is not only preferred by the elderly to institutionalized care or hospitalization, but is also the cheapest of available solutions.